Diseño de un sistema de control interno para hacer el seguimiento de los diferentes recursos que se utilizan durante la prestación de un servicio de Mud Logging (2017)
In the present work an internal inventory control system for a Mud Logging line will be proposed, the concepts of this service line, its functions and objectives within the drilling operation in an oil field will be clarified, the activities to be performed by each of its employees and the importance of the good performance of the personnel that make it up. After having clear the concept of the line of service to work, key characteristics of an internal control system will be mentioned, in order to provide the reader with the basic knowledge for understanding the development of the topic.